miR-150-5p and XIST interaction controls monocyte adherence: Implications for osteoarthritis therapy - Wang, Yu-Han; Tsai, Chun-Hao; Liu, Shan-Chi; Chen, Hsien-Te; Chang, Jun-Way; Ko, Chih-Yuan; Hsu, Chin-Jung; Chang, Ting-Kuo; Tang, Chih-Hsin (Frontiers in Immunology, 2022)
Recent literature highlights the importance of microRNAs (miRNAs) functioning as diagnostic biomarkers and therapeutic agents in osteoarthritis (OA) and regulators of gene expression. In OA pathogenesis, cell adhesion molecules (CAMs), especially vascular cell adhesion protein 1 (VCAM-1), recruit monocyte infiltration to inflamed synovial tissues and thus accelerate OA progression. Up until now, little has been known about the regulatory mechanisms between miRNAs, long non-coding RNAs (lncRNAs) and VCAM-1 during OA progression. The evidence in this article emphasizes that the functional feature of miR-150-5p is an interaction with the lncRNA X-inactive specific transcript (XIST), which regulates VCAM-1-dependent monocyte adherence in OA synovial fibroblasts (OASFs). Levels of VCAM-1, CD11b (a monocyte marker) and XIST expression were higher in human synovial tissue samples and OASFs, while levels of miR-150-5p were lower in human OA synovial tissue compared with non-OA specimens. XIST enhanced VCAM-1-dependent monocyte adherence to OASFs. Upregulation of miR-150-5p inhibited the effects of XIST upon monocyte adherence. Administration of miR-150-5p effectively ameliorated OA severity in anterior cruciate ligament transection (ACLT) rats. The interaction of miR-150-5p and XIST regulated VCAM-1-dependent monocyte adherence and attenuated OA progression. Our findings suggest that miR-150-5p is a promising small-molecule therapeutic strategy for OA.